Respuesta a niveles de nitrógeno, fosforo y potasio en el cultivo de maíz (Zea mays, L), en condiciones de la zona de Babahoyo - Aguilar Castro, Alvaro Jasmany (2019)
VIII. SUMMARY The present research work was developed in the Mariana enclosure located on the Montalvo - Babahoyo road, which has the following geographic coordinates UTM X: 1.7723946; Y: 79.7102593, with an annual rainfall of 2200 mm, with a relative humidity of 65 to 80%, a heliophany of 7 daily light hours and a temperature of 24 degrees Celsius. As planting material Hybrid Dekalb 7088 was used, which is more adapted to the area and reaches genetic maturity at 120 days. The treatments were constituted by the different levels of fertilizers such as: 60% (40% efficiency NPK), 40% (60% efficiency NPK), 20% (80% efficiency NPK), 10% (90% efficiency NPK), 60 % N (40% efficiency N); plus a treatment with application of base fertilization. We used the experimental design Random Complete Blocks with six treatments and 4 repetitions, the test of significance used was Tukey at 95% probability. All the necessary agricultural work was done in the corn crop for its normal development as soil preparation, sowing, fertilization, weed control, phytosanitary control and harvesting. To estimate the effects of the treatments, the following data were taken: plant height, ear insert height, stem diameter, ear length, ear diameter, leaf area, weight of 100 grains, yield, economic analysis. From the results obtained it was determined that the soil fertilizers applied in the treatments T2, T3, T4, T5 and T6 did not show statistical differences in the height with respect to the T1 planted with a basic fertilization plan. The treatment T2 at a dose of 60% (40% efficiency N-P-K) reacted in a superior way than the treatments T1, T3, T4, T5 and T6 with the height of the insertion of the ear. In the weight of 100 seeds the treatment T2 at a dose of 60% (40% efficiency NPK), obtained a significant difference with respect to the rest of the treatments, T6 at a dose of 60% N (40% efficiency N) presented the lower value inclusive than T1. The best performance obtained was the T2 treatment, where it reached 5510 kg / ha, unlike the lowest value with the T5 treatment with 4940 kg / ha.